Risk for Tympanic Membrane Perforation After Quinolone Ear Drops for Acute Otitis Externa. (2nd May 2019) - Wang, Xi; Winterstein, Almut G; Alrwisan, Adel; Antonelli, Patrick J
Abstract: Background: This study examined whether the use of quinolone ear drops increased the risk of perforation with intact tympanic membranes and acute otitis externa (AOE). Methods: This was a retrospective cohort study using Medicaid clinical encounter and pharmacy billing records from 1999 through 2010. Children and adults had to have 24 months continuous enrollment in Medicaid prior to the first antibiotic ear drop dispensing (index date), and they had to maintain their enrollment for at least 18 months thereafter. Included ear drops were ofloxacin, ciprofloxacin plus hydrocortisone, ciprofloxacin plus dexamethasone, and neomycin plus hydrocortisone. Tympanic membrane perforation (TMP) was identified as 2 inpatient or outpatient encounters associated with TMP diagnosis at least 30 days apart. A Cox regression model adjusting for patient demographics, calendar year, and the number of ear drop prescriptions was used to compare TMP risk between quinolone and neomycin-exposed patients. Results: A total of 94 333 patients entered the study cohort. Use of quinolone ear drops was associated with increased risk for TMP compared with neomycin plus hydrocortisone, with an adjusted hazard ratio of 2.26 (95% confidence interval [CI], 1.34–3.83). Adjusted hazard ratios were 2.53 (95% CI, 1.27–5.05) for ofloxacin, 2.24 (95% CI, 1.03–4.85) for ciprofloxacin plus hydrocortisone, and 2.30 (95% CI, 1.09–4.87) for ciprofloxacin plus dexamethasone. Sensitivity analyses were consistent with the primary analysis. Conclusions: Use of quinolone ear drops to treat AOE is associated with a previously unreported increased risk of developing TMPs. Selection of otic preparations to treat self-limited conditions with intact tympanic membranes should consider TMP risk. Abstract : This is the first comparative safety study of ototopical fluoroquinolones for treating acute otitis externa in real-world clinical practice. Our findings reinforce the notion that risk-benefit of quinolone ear drops should be carefully evaluated.